(i, j)-ω-b-OPEN SETS AND (i, j)-ω-b-CONTINUITY IN BITOPOLOGICAL SPACES - Carpintero, Carlos; Hussain, Sabir; Rosas, ennis (Italian Journal of Pure and Applied Mathematics, 2015)
As a generalization of (i,j)-b-open sets in bitopological spaces, we introduce and explore the notions of (i, j)-ω-b-open sets. We also develop its relationship with already defined generalizations of b-open sets. Moreover we define and discuss the properties of (i, j)-ω-b-continuous functions.